Cost-Effectiveness of a JAK1/JAK2 Inhibitor vs a Biologic Disease-Modifying Antirheumatic Drug (bDMARD) in a Treat-to-Target Strategy for Rheumatoid Arthritis - Van De Laar CJ; Oude Voshaar MAH; Fakhouri WKH; Zaremba-Pechmann L; De Leonardis F; De La Torre I; Van De Laar MAFJ (Dove Medical Press, 2020)
Celine J Van De Laar,1 Martijn AH Oude Voshaar,1,2 Walid KH Fakhouri,3 Liliana Zaremba-Pechmann,3 Francesco De Leonardis,3 Inmaculada De La Torre,3 Mart AFJ Van De Laar1,2 1Transparency in Healthcare BV, Hengelo, the Netherlands; 2Department of Psychology and Communication of Health and Risk, Institute for Behavioural Research, University of Twente, Enschede, the Netherlands; 3Eli Lilly & Company, Indianapolis, IN, USACorrespondence: Celine J Van De Laar Tel +31 74-43032645Email c.vandelaar@tihealthcare.nlBackground: Baricitinib is a janus kinase (JAK1/JAK2) inhibitor developed for the treatment of patients suffering from rheumatoid arthritis (RA). Treating RA to the target of remission is current common practice. Cost-effectiveness of different treat-to-target (T2T) strategies, especially ones including new treatments is important for development and preference policy for treatment centers. European League Against Rheumatism (EULAR) and American College of Rheumatology (ACR) guidelines are currently unclear about preference between a JAK1/JAK2 versus a biological disease-modifying antirheumatic drug (bDMARD).Objective: The main goal of this paper was to evaluate the cost-effectiveness of baricitinib versus first biological for methotrexate inadequate responders in a T2T strategy using a Markov model that incorporates hospital costs as well as societal costs. Costs and utilities over five years were compared between the two strategies.Methods: A Monte Carlo simulation model was developed to conduct cost–utility analysis from the societal perspective over 5 years. Health states were based on the DAS28-erythrocyte sedimentation rate (ESR) categories. Effectiveness of baricitinib was retrieved from randomized controlled trials. Effectiveness of all other treatments, health state utilities, medical costs, and productivity loss were retrieved from the Dutch RhEumatoid Arthritis Monitoring (DREAM) cohorts. Annual discount rates of 1.5% for utility and 4% for costs were used. Probabilistic sensitivity analysis was employed to incorporate uncertainty and assess robustness of the results.Results: Probabilistic sensitivity analysis results showed the baricitinib strategy yielded lower costs and higher utility over a 5-year period. Scenario analyses showed the baricitinib strategy to be cost-effective in both the moderate and severe RA populations.Conclusion: Results suggest that the use of a JAK1/JAK2 inhibitor instead of a bDMARD in a T2T approach is cost-effective in csDMARD refractory RA patients.Keywords: Markov model, rheumatoid arthritis, baricitinib, cost-effectiveness, health economic model, treat-to-target